Physical characterization, magnetic measurements, REE geochemistry and biomonitoring of dust load accumulated during a protracted winter fog period and their implications - Chakarvorty, Munmun; Pati, Jayanta Kumar; Patil, S. K.; Shukla, Swati; Niyogi, Ambalika; Saraf, Arun Kumar (My University, 2014)
The winter fog in India is a recurrent phenomenon for more than a decade now affecting the entire Himalayan and sub-Himalayan regions covering an area of nearly 500,000 km2. Every winter (December–January), the air and surface transports in cities of northern India (Amritsar, New Delhi, Agra, Gwalior, Kanpur, Lucknow, and Allahabad) are severely disrupted with visibility reduced to <50 m at times. Since dust particles are known to act as nuclei for the fog formation, this study is aimed to carry out physicochemical characterization of the dust particulates accumulated during a protracted fog period from one of the severely fog affected cities of north India (Allahabad; 25°27′33.40″N–81°52′45.47″E). The dust-loaded tree leaves belonging to Ficus bengalensis and Ficus religiosa from 50 different locations between January 24 and 31, 2010 are sampled and characterized. The mass of dust, color, grain shape, size, phase constituents, and mineral magnetic parameters, such as magnetic susceptibility, SIRM, χ fd%, and S-ratio, show minor variation and the regional influence outweighs local anthropogenic contributions. The dust compositions show fractionated rare earth element pattern with a pronounced negative Eu anomaly similar to upper continental crust and further suggesting their derivation from sources located in parts of north and central India.
Keywords: Physical characterization; Particulate matter; Magnetic susceptibility; Winter fog; Biomonitoring; Geochemistry